2007
DOI: 10.1093/pasj/59.4.l25
|View full text |Cite
|
Sign up to set email alerts
|

Detection of a Long-Extended Dust Trail Associated with Short-Period Comet 4P/Faye in 2006 Return

Abstract: The longest dust trail among those so detected at optical wavelengths was found along the orbit of 4P/Faye in the 2006 return. It extended as long as 10° in the backward direction. The surface brightness increases monotonically with the distance from the nucleus between $0\rlap{.}^\circ5$ and 3°, but decreases slowly beyond 4°. The observed brightnesses of the dust trail and the tail are reasonably explained by our dust ejection model. The model shows that the dust trail is composed of cm-sized particles eject… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 7 publications
0
10
0
Order By: Relevance
“…Moreno et al (2008) studied the morphology of the dust cloud in terms of the dynamics of the particles, and found that >600 μm particles, which are much less sensitive to radiation pressure than micrometersized or smaller particles, could be ejected by the outburst. Evidence of such large particles is found to be ubiquitous in in situ observations (McDonnell et al 1986;Tuzzolino et al 2003), by the remote sensing observations of dust tail (Fulle 2004;Moreno 2009;Watanabe et al 1990) and dust trail Ishiguro 2008;Sarugaku et al 2007;Reach et al 2000Reach et al , 2007Kelley et al 2008), sub-millimeter and millimeter observations (Jewitt & Matthews 1997;Altenhoff et al 1999). As a result of these studies, we found that the power index of the size distribution of almost all comets would be in the range of −4 and −3 (Fulle 2004).…”
Section: Mass Erosionmentioning
confidence: 97%
“…Moreno et al (2008) studied the morphology of the dust cloud in terms of the dynamics of the particles, and found that >600 μm particles, which are much less sensitive to radiation pressure than micrometersized or smaller particles, could be ejected by the outburst. Evidence of such large particles is found to be ubiquitous in in situ observations (McDonnell et al 1986;Tuzzolino et al 2003), by the remote sensing observations of dust tail (Fulle 2004;Moreno 2009;Watanabe et al 1990) and dust trail Ishiguro 2008;Sarugaku et al 2007;Reach et al 2000Reach et al , 2007Kelley et al 2008), sub-millimeter and millimeter observations (Jewitt & Matthews 1997;Altenhoff et al 1999). As a result of these studies, we found that the power index of the size distribution of almost all comets would be in the range of −4 and −3 (Fulle 2004).…”
Section: Mass Erosionmentioning
confidence: 97%
“…Although there are many factors to determine the expansion dust speed, it can be approximated by a simple power-law function of the size and the heliocentric distance, that is, v ej = K/ √ r h a d , where a d denotes the radius of dust particles in micron. K is a constant, typically in the range of 100 < K < 1000 m s −1 based on theoretical studies (Whipple 1951;Ip & Mendis 1974), past observations of normal comet activities (Lisse et al 1998;Ishiguro et al 2007;Sarugaku et al 2007;Snodgrass et al 2008;Ishiguro 2008), and cometary outbursts including the 17P/Holmes event in 2007 (Sekanina 2008;Montalto et al 2008;Moreno et al 2008;Hsieh et al 2010;Sarugaku et al 2010;Reach et al 2010;Stevenson & Jewitt 2012). From the equation for the expanding speed, dust particles could escape from a region of 1 ′′ aperture in 1.4-22 hours for a d = 1 µm and 6-94 days for a d = 1 cm particles.…”
Section: Radial Profilesmentioning
confidence: 99%
“…A three-dimensional analysis, which allows nonzero ejection velocities to be considered, is appropriate to estimate the particle sizes and mass-loss rate. Here we applied a three-dimensional analysis to match the observed images, following the model in Ishiguro et al (2007), Sarugaku et al (2007), Ishiguro (2008), and Hanayama et al (2012).…”
Section: Dust Tail Morphologymentioning
confidence: 99%
“…The sky background was contaminated by elongated stars and galaxies because the observations were carried out in comet-tracking mode. We removed these stellar objects using the masking algorism developed for the data reduction of cometary dust trails (Sarugaku et al 2007;Ishiguro et al 2007;Ishiguro 2008), outlined as follows. We first made images to align the stars, because this is an effective way of detecting faint stars and galaxies.…”
Section: Data Reductionmentioning
confidence: 99%
“…No obvious dust trail was found in the Subaru optical image, even though it was clear in the Spitzer infrared image. In this study, we re-analyzed the Subaru/Suprime-Cam images using the masking method developed for the detection of faint cometary dust clouds (Ishiguro et al 2007;Sarugaku et al 2007;Ishiguro 2008) and constructed a comet image without contaminants (e.g., stars and galaxies). This technique enabled us to detect mini-comets brighter that 26.5 mag and diffuse light sources associated with the comet brighter than 30.0 mag arcsec -2 .…”
mentioning
confidence: 99%